Analysis of volatile compounds in gluten-free bread crusts with an optimised and validated SPME-GC/QTOF methodology. (April 2018) - Pico, Joana; Antolín, Beatriz; Román, Laura; Gómez, Manuel; Bernal, José
Abstract: The aroma of bread crust, as one of the first characteristics perceived, is essential for bread acceptance. However, gluten-free bread crusts exhibit weak aroma. A SPME-GC/QTOF methodology was optimised with PCA and RSM and validated for the quantification of 44 volatile compounds in bread crust, extracting 0.75 g of crust at 60 °C for 51 min. LODs ranged between 3.60 and 1760 μg Kg −1, all the R 2 were higher than 0.99 and %RSD for precision and %Er for accuracy were lower than 9% and 12%, respectively. A commercial wheat bread crust was quantified, and furfural was the most abundant compound. Bread crusts of wheat starch and of japonica rice, basmati rice and teff flours were also quantified. Teff flour and wheat starch crusts were very suitable for improving gluten-free bread crust aroma, due to their similar content in 2-acetyl-1-pyrroline and 4-hydroxy-2, 5-dimethyl-3(2H)-furanone compared to wheat flour crust and also for their high content in pyrazines. Graphical abstract: Unlabelled Image Highlights: A SPME-GC/QTOF method was developed and optimised for analysing bread crust aroma. SPME conditions implied 0.75 g of crust sample extracted at 60 °C for 51 min. The proposed SPME-GC/QTOF methodology was sensible, precise, accurate and linear. Furfural was the most abundant compound in commercial wheat bread crust. Teff and wheat starch crusts showed contents of 2-ACPY close to wheat crust.